2022
DOI: 10.1002/cbdv.202200327
|View full text |Cite
|
Sign up to set email alerts
|

Cu‐Catalyzed Chan–Evans–Lam Coupling Reactions of 2‐Nitroimidazole with Aryl Boronic Acids: An Effort toward New Bioactive Agents against S. pneumoniae

Abstract: The coupling of phenylboronic acids with poorly-activated imidazoles is studied as a model system to explore the use of copper-catalyzed Chan -Evans-Lam (CEL) coupling for targeted CÀ N bond forming reactions. Optimized CEL reaction conditions are reported for four phenanthroline-based ligand systems, where the ligand 4,5-diazafluoren-9-one (dafo, L2) with 1 molar equivalent of potassium carbonate yielded the highest reactivity. The substrate 2-nitroimidazole (also known as azomycin) has documented antimicrobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Based on the trials discussed in Table S1, † Cu 2+ BIM was further optimized using different additive bases as listed in Table 2. In a previous report, 45 it was noted that the addition of a slight excess of potassium carbonate improved the reactivity of CEL systems. We found that the addition of potassium carbonate to our reactions increased the conversion with the prepared catalyst Cu 2+ BIM when between 0.5 and 2.0 molar equivalents were added (Table 2, entries 1-3).…”
Section: Dalton Transactions Papermentioning
confidence: 90%
“…Based on the trials discussed in Table S1, † Cu 2+ BIM was further optimized using different additive bases as listed in Table 2. In a previous report, 45 it was noted that the addition of a slight excess of potassium carbonate improved the reactivity of CEL systems. We found that the addition of potassium carbonate to our reactions increased the conversion with the prepared catalyst Cu 2+ BIM when between 0.5 and 2.0 molar equivalents were added (Table 2, entries 1-3).…”
Section: Dalton Transactions Papermentioning
confidence: 90%
“…The reactivity of electronrich anilines was found to be higher than that of electrondeficient ones. The reaction of alkyl amines was similar to that of anilines, while secondary alkylamine, N-methyl hexylamine, and N-methyl aniline completely failed to give 40 The targeted C-N coupling was achieved by reacting 2-nitro imidazoles with aryl boronic acid in the presence of 8 mol% Cu(OTf) 2 , 1 equiv. of the ligand 4,5-diazafluoren-9-one (dafo), and 1 equiv.…”
Section: Catalysis Science and Technology Reviewmentioning
confidence: 98%
“…Emerson et al successfully established the Chan–Evans–Lam coupling between inactive imidazoles and aryl boronic acids in 2022. 40 The targeted C–N coupling was achieved by reacting 2-nitro imidazoles with aryl boronic acid in the presence of 8 mol% Cu(OTf) 2 , 1 equiv. of the ligand 4,5-diazafluoren-9-one (dafo), and 1 equiv.…”
Section: Classificationmentioning
confidence: 99%
“…The organic motifs, framework, and donor atom set of these complexes all wield pivotal roles in their chemistry [8,9]. These coordination complexes have also found extensive utility in catalysis, with numerous research groups delving into their catalytic properties across a wide spectrum of processes, including oxidation reactions [10], atom transfer reactions [11,12], Chan-Evans-Lam reactions [13][14][15][16], Ullmann and Goldberg-type couplings [17], and click reactions [18,19].…”
Section: Introductionmentioning
confidence: 99%